Effects of substituting medium chain fatty acids (MCFA) for carbadox and zinc oxide (ZnO) on weanling pig performance - Vanderee, Tessa D.; Lerner, Anne B.; Jones, Cassandra K. (My University, 2019)
There is consumer pressure to remove use of carbadox and ZnO from weanling pig diets. This experiment tests the effects of MCFA’s versus carbadox and ZnO on weanling pig growth when compared to an unmedicated control group. A total of 360 weanling pigs (DNA 200*400; 5.4 ±0.06kg BW; 21 d age) were used in a 35-d experiment using 6 treatments with 10 pens per treatment using the grouped completely randomized design. The treatments were 1) Control 2) ZnO (3000 ppm in phase 1 and 1500 ppm in phase 2); 3) 50g/ton carbadox; 4) 1% blend C6:C8:C10; 5) 1% feed energy R2 (Feed Corp Demoin, IA); 6) 1% FORMI GML (ADDCON, Bitterfeld-Wolfen, Germany). Phase 1 diets were fed days 0 to 7, phase 2 diets days 8 to 19 and a common diet was fed from days 20 to 35. Pigs and feeders were weighed to calculate ADG, ADFI and G: F. Data was analyzed with PROC GLIMMIX (SAS version 9.4 Cary, NC). During treatment (d 0-19), pigs fed FORMI showed similar (P>0.05) ADG and ADFI to pigs fed ZnO and carbadox, while those fed R2 had lower ADG (P>0.05) when compared to those fed ZnO and carbadox. Overall (d 0-35) pigs fed ZnO had greater (P<0.05) ADG than pigs fed R2. There was no difference (P>0.05) in ADG between pigs fed ZnO, carbadox, C6:C8:C10, FORMI or the control. Pigs fed ZnO and carbadox had statistically higher (P<0.05) ADFI than pigs fed R2. There were no observed differences (P>0.05) between pigs fed ZnO, carbadox, C6:C8:C10, FORMI or the control. Ultimately pigs fed FORMI showed similar ADG and ADFI to pigs fed ZnO and carbadox in both the treatment (0-19) and the overall (0-35). However, pigs fed R2 showed consistently lower ADG and ADFI than those fed ZnO in both time periods
Keywords: Spring 2019